The Effect of BPJS Service Quality Level and Patient Characteristics to Patient Satisfaction in Primary Health Facilities - Yogi Bhakti Marhenta; Satibi Satibi; Chairun Wiedyaningsih (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Health services in the era of JKN are organized by all Health Facility in cooperation with BPJS. Patient satisfaction is a critical indicator whether a program is a success or not. Satisfaction is the pleasure of someone who comes from the comparison between a product or performance with expectations, if performance is below expectations then the customer is not satisfied. This study aims to determine the effect of membership, service, and financing of patient satisfaction with BPJS in Primary Health Facilities. This research is an analytical descriptive research with cross sectional survey design. The data was taken quantitatively by using questionnaires and completed with qualitative data through interviews to deepen the findings of the field. Sampling technique used is purposive sampling with inclusion criteria. The number of respondents samples used were 278 respondents and the sample of the study sites was determined by random sampling method including health center, clinic and pharmacy network. The data were analyzed by using multiple linear regression analysis in the form of t test and F test. The result of research at Primary Health Facilities Regency showed that there was positive and significant influence to patient satisfaction of BPJS, including membership variable (p = 0,02), variable of service (p = 0,00), and financing variable (p = 0,00), while F test simultaneously also shows there are positive and significant influence to patient satisfaction BPJS with value (p = 0,00).